Etika informasi dan perpustakaan di era digital: Tantangan hoax dan penggunaan yang bertanggung jawab dalam media sosial - Maulidia, Suci (Maliki Interdisciplinary Journal, 2024)
The advancement of digital technology has significantly impacted human life, altering the way we interact, access information, and utilize social media. This article discusses the challenges and impacts of the phenomenon of hoaxes in the digital era, as well as the crucial role of libraries in addressing this issue. Hoaxes, or disinformation, harm society by disseminating false information that can damage the reputation of individuals or groups, incite conflicts, and influence public perception. To combat hoaxes, public awareness to verify information before spreading it is necessary, along with strict legal actions against hoax perpetrators. Additionally, this article highlights the importance of responsible use of social media, where individuals must understand and apply ethics in online communication. Libraries serve as reliable sources of information and can assist the community in seeking accurate information, as well as providing education on information ethics and responsible social media use. Through training, collaboration with educational institutions, and community events, libraries have the potential to become crucial educational centers in addressing the challenge of hoaxes and promoting wise internet usage in the digital era.